Place of the Advanced Practice Registered Nurse within the vascular team: a qualitative study of vascular medicine physicians and nurses caring for patients with peripheral artery disease. (3rd October 2022) - Kubiak, T; Sitruk, J; Khider, L; Durivage, A; Mortelette, H; Mohamedi, N; Detriche, G; Messas, E; Mirault, T; Goudot, G
Abstract: Introduction: Advanced Practice Registered Nurses (APRNs) treat and diagnose diseases, counsel the public about health problems, manage chronic diseases, and participate in continuing education. In the cardiovascular field, Peripheral Arterial Disease (PAD), one of the manifestations of atherosclerotic cardiovascular disease, is archetypal in combining multiple cardiovascular risk factors (hypertension, hyperlipidemia, diabetes mellitus smoking). Vascular medicine faces the challenge of improving their care and quality of life, but some goals cannot be achieved with all patients. Patients with PAD should benefit from APRN care, but to date there is little published on the place of APRN in vascular medicine worldwide, and none in France. Objective: It appeared important to us to assess the perception of their role by physicians and nurses in vascular medicine. As the status of APRN in France has only been enacted by law in 2018, we aim to investigate physicians and nurses working with patients suffering from PAD, to gather their opinions and draw the cooperation outlines these practitioners could have with an APRN. Methods: Multicentre exploratory qualitative study by semi-directive interview conducted until data saturation and thematic analysis carried out with healthcare practitioners taking care of patients with PAD: 10 physicians working either in private practice setting or hospital setting or both, and 8 nurses in a vascular unit for hopsitalised patients. Results: Three main themes emerged from responders' verbatims: a specific organization of vascular medicine with its inherent challenges, particularly regarding patients with PAD (specific psychosocial profile of patients, lack of therapeutic education, time, knowledge of non-specialist physicians, tedious follow-up outside hospitals, complex care trajectory, and lack of medical-surgical collaboration). Second, a role for APRN, particularly in consultation as part of patient follow-up, with expected benefits for the patient and the care team. The APRN is wanted to fill part of this gap. The expected benefits include a smoother care pathway and increased capacity for cardiovascular education and prevention, especially during consultations. Third, there are certain pitfalls that need to be clarified to integrate these new practitioners into the vascular teams already in place. In particular, the need to inform the vascular medicine teams about this new profession, and the indispensable presence of the conditions necessary for the development of a relationship of trust. Conclusion: APRN could be the missing link in a Vascular team by creating a continuum in the care of patients with PAD, ensuring clinical assessment, nursing supervision, adverse event screening, and renewing drug prescriptions with the necessary adjustments, while ensuring an essential part of therapeutic education personalized to each PAD patient. Funding Acknowledgement: Type of funding sources: None.